Political Communication in the Time of Coronavirus (Taylor & Francis, 2021)
Covid-19, beliefs, public communication, Sweden, ideology, citizens, news media, media use, pandemic, coronavirus
English
Keywords: Media studies; Political structure & processes; Press & journalism; Covid-19, beliefs, public communication, Sweden, ideology, citizens, news media, media use, pandemic, coronavirus